2014
DOI: 10.1051/0004-6361/201424509
|View full text |Cite
|
Sign up to set email alerts
|

Keplerdetection of a new extreme planetary system orbiting the subdwarf-B pulsator KIC 10001893

Abstract: KIC 10001893 is one out of 19 subdwarf-B (sdB) pulsators observed by the Kepler spacecraft in its primary mission. In addition to tens of pulsation frequencies in the g-mode domain, its Fourier spectrum shows three weak peaks at very low frequencies, which is too low to be explained in terms of g modes. The most convincing explanation is that we are seeing the orbital modulation of three Earth-size planets (or planetary remnants) in very tight orbits, which are illuminated by the strong stellar radiation. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 44 publications
0
63
0
Order By: Relevance
“…A few additional companions to hot stars or remnants have been announced from the Kepler mission via transits, pulsation timing, or Doppler beaming (e.g., Silvotti et al 2007Silvotti et al , 2014Charpinet et al 2011;Ahlers et al 2015;Murphy et al 2016). Finally, several directly imaged planets orbiting young stars with T 7500 K eff  have been announced, 41 the three hottest of which have very large uncertainties in the masses and radii of the planets owing to the uncertain age of their parent stars, which may put them in the brown dwarf regime (Acke & van den Ancker 2006;Lafrenière et al 2011;Carson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A few additional companions to hot stars or remnants have been announced from the Kepler mission via transits, pulsation timing, or Doppler beaming (e.g., Silvotti et al 2007Silvotti et al , 2014Charpinet et al 2011;Ahlers et al 2015;Murphy et al 2016). Finally, several directly imaged planets orbiting young stars with T 7500 K eff  have been announced, 41 the three hottest of which have very large uncertainties in the masses and radii of the planets owing to the uncertain age of their parent stars, which may put them in the brown dwarf regime (Acke & van den Ancker 2006;Lafrenière et al 2011;Carson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Examples are the 1.25 MJ planet (where MJ is the mass of Jupiter) orbiting 0.116 au from a horizontal branch star (Setiawan et al 2010), two Earth-sized objects orbiting a subdwarf B star at a separation of 0.0060 and 0.0076 au (Charpinet et al 2011), or three earth-sized planets orbiting a subdwarf B pulsator (Silvotti et al 2014). These planets must have been engulfed in the envelope of the giant star that became the subdwarf star today.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Kepler data were carefully reduced and there are no known artefact frequencies within this region, we concluded that both planetary signature frequencies (and perhaps a couple of others) observed beyond the cut-off frequency limits are most likely of pulsation origin. The example of KIC 5807616 also has implications for other claims of extreme planetary systems around sdB stars based on similar assumptions of the strict cut-off frequency limits for the pulsating modes (Silvotti et al 2014, KIC 10001893 sdBV), which might need to be reanalysed in a similar way to how it has been done in this paper.…”
Section: Discussionmentioning
confidence: 80%